High-Temperature Short-Time Treatment of Human Milk for Bacterial Count Reduction - Klotz, Daniel; Schreiner, Marie; Falcone, Valeria; Jonas, Daniel; Kunze, Mirjam; Weber, Andrea; Fuchs, Hans; Hentschel, Roland (Frontiers in Pediatrics, 2018)
Background: Human milk (HM) for preterm infants will often be pasteurized for cytomegalovirus (CMV) inactivation and reduction of its bacterial count. High-temperature short-time (HTST) treatment compared to standard Holder pasteurization (HoP) reduces the impact of heat treatment on bioactive HM proteins while effectively inactivating CMV. No data are available for the efficacy of bacterial count reduction using HTST treatments that are available for clinical use. Objective: To test the antiviral and antibacterial efficacy of HTST treatment protocols in HM using a modified HTST treatment device compared to standard HoP. Methods: Holder pasteurized 95 mL HM samples were inoculated with Staphylococcus aureus (ATCC 6538), Enterococcus faecalis (ATCC 29212), Pseudomonas aeruginosa (ATCC 27853), Serratia marcescens (Smarc 00697), two different strains of Klebsiella pneumoniae (ATCC 700603 and Kpn 01605) or spiked with 2 x 105 50% tissue culture infective dose of CMV (AD169) and subsequently subjected to HoP (62.5°C/30 min) or HTST treatment (62°C/5s, 62°C/15s, 72°C/5s, 72°C/15s, 87°C/2s and 87°C/5s). Bacterial count was determined after treated HM was cultured for 24h. CMV infectivity was determined by the number of specific CMV immediate early antigen stained nuclei after inoculating human fibroblasts with appropriately prepared HM samples. Results: Holder pasteurized samples revealed no growth after 24h incubation. Viable bacterial cultures were retrieved from all tested strains after HTST treatment with the default HTST protocol (62°C/5s) that is available for clinical use. Using other time-temperature combinations, growth rates of S. aureus, E. faecalis, P. aeruginosa, K. pneumoniae, K. pneumoniae and S. marcescens were depending on treatment time, treatment temperature, bacterial genera and strain. Only after treatment temperatures above 72°C no bacterial growth was observed. CMV was inactivated by any tested time-temperature combination. Conclusions: HTST treatment inactivates CMV in 95 mL HM samples but is less effective than HoP in bacterial count reduction at a time-temperature combination of 61°C/5s. For a reliable bacterial count reduction HTST treatment at 87°C was required in this study.